Extraction of Bioactive Compounds as Natural Antioxidants from Fresh Spirulina platensis using Different Solvents - Fiya Firdiyani; Tri Winarni Agustini; Widodo Farid Ma'ruf (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2015)
Spirulina platensis is a bioactive-rich microalga of great potential as a source of natural antioxidant. Natural antioxidants are increasing in demand, because it is considered as more safe than synthetic antioxidants. The objective of this study was to determine the effect of solvent on the potential of natural antioxidant from fresh S. platensis. The antioxidant compound was extracted using either acetone or ethyl acetate by reflux method. The yield of extractions were 1.86% and 3.07% for aceton and ethyl acetate, respectively. Fresh S. platensis extracts were considered as potential antioxidant source with IC50 values 65.89 ppm, and 76.36 ppm when using acetone and ethyl acetate, respectivetly, even though it were still lower compare to the IC50 of positive control quercetin i.e 21.64 ppm. Phytochemical test showed positive results of phenolic compound, triterpenoids, steroid, flavanoid, and saponin. aw value of Spirulina platensis was 0.61 and 0.81 for aceton and ethyl acetate, respectively. It was concluded that different solvent affected the antioxidant activity of S. platensis extract. Keywords: Antioxidants, aceton, ethyl acetate, fresh Spirulina platensis